It's not news, it's fark : how mass media tries to pass off crap as news - Curtis, Drew (New York : N.Y, 2007)
"While comedy shows report funny fake news, Fark.com features funny real news. On slow news days, mainstream media still has to deliver. Fark founder Drew Curtis has noticed several distinct patterns used to turn non-news into the news you see each day. These include: fear-mongering in the absence of facts; the bogus press release, which states a new finding but fails to explain where the numbers came from; media fatigue, when the media exhaust every angle of an existing story rather than digging for something new; and the coverage given to such events as brides who don't want to get married, fake their own kidnapping, and escape cross-country. Such non-news should appear only once, if at all, in mainstream media. So why are we overexposed to such schlock from legitimate news outlets?--From publisher description.
"What is fark? -- Media fearmongering -- Unpaid placement masquerading as actual article -- Headline contradicted by actual article -- Equal time for nut jobs -- The out-of-context celebrity comment -- Seasonal articles -- Media fatigue -- Lesser media space fillers -- Epilogue: What should mass media be doing instead?
Includes index
Keywords: Mass media -- United States